Coronary angioplasty in the acute phase of myocardial infarct. - Gabriel, H M (1998)
Primary coronary angioplasty is a reperfusion method increasingly used for the treatment of acute myocardial infarction. Several studies are reviewed, demonstrating a reduction in mortality and morbidity, namely due to recurrent ischaemia and haemorrhagic stroke, in comparison to thrombolysis. This benefit seems larger in high risk patients, such as those with cardiogenic shock, anterior wall infarction, elderly patients and those with contraindications thrombolysis or with a non diagnostic electrocardiogram.